2023
DOI: 10.1021/acs.jmedchem.3c00182
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Attribution of the Protective Effects of Aminosterols against Protein Aggregates to Their Chemical Structures and Ability to Modulate Biological Membranes

Abstract: Natural aminosterols are promising drug candidates against neurodegenerative diseases, like Alzheimer and Parkinson, and one relevant protective mechanism occurs via their binding to biological membranes and displacement or binding inhibition of amyloidogenic proteins and their cytotoxic oligomers. We compared three chemically different aminosterols, finding that they exhibited different (i) binding affinities, (ii) charge neutralizations, (iii) mechanical reinforcements, and (iv) key lipid redistributions wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
5
3
0
Order By: Relevance
“…1) allowed us to obtain the corresponding K D values (Figure 5C). The K D values obtained with this LUVs composition were comparable to those obtained in a previous work with a very similar lipid composition, except a lower concentration of CHOL 63 . SQ was confirmed to have a higher increase of fluorescence upon LUV binding, and a higher affinity for LUVs, as showed by the lower K D value of 0.013 ± 0.002 mg/ml (corresponding to a ΔG value of -27.36 ± 0.69 kJ mol -1 ), compared to 0.034 ± 0.004 mg/ml for TRO (corresponding to a ΔG value of -24.93 ± 0.47 kJ mol -1 ).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…1) allowed us to obtain the corresponding K D values (Figure 5C). The K D values obtained with this LUVs composition were comparable to those obtained in a previous work with a very similar lipid composition, except a lower concentration of CHOL 63 . SQ was confirmed to have a higher increase of fluorescence upon LUV binding, and a higher affinity for LUVs, as showed by the lower K D value of 0.013 ± 0.002 mg/ml (corresponding to a ΔG value of -27.36 ± 0.69 kJ mol -1 ), compared to 0.034 ± 0.004 mg/ml for TRO (corresponding to a ΔG value of -24.93 ± 0.47 kJ mol -1 ).…”
Section: Resultssupporting
confidence: 87%
“…We performed binding experiments incubating 10 μM of each labelled aminosterol for 15 min with increasing concentrations of unlabeled LUVs. Both TRO and SQ displayed a significant increase in fluorescence emission in the presence of LUVs (Figure 5C), as previously observed 63 and fitting the data points to a standard binding curve (Eq. 1) allowed us to obtain the corresponding K D values (Figure 5C).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Numerous studies have shown that once integrated into a membrane the spatial organization of lipids within the membrane, fluidity, and tensile strength are altered 37 . Because squalamine electrostatically reduces the overall surface charge of the membrane, the function of membrane proteins positioned by electrostatic forces can be affected.…”
Section: Discussionmentioning
confidence: 99%